Diuretic Action of Apelin-13 Mediated by Inhibiting cAMP/PKA/sPRR Pathway - Chen, Yanting; Xu, Chuanming; Hu, Jiajia; Deng, Mokan; Qiu, Qixiang; Mo, Shiqi; Du, Yanhua; Yang, Tianxin (Frontiers in Physiology, 2021)
Emerging evidence is showing that apelin plays an important role in regulating salt and water balance by counteracting the antidiuretic action of vasopressin (AVP). However, the underlying mechanism remains unknown. Here, we hypothesized that (pro)renin receptor (PRR)/soluble PRR (sPRR) might mediate the diuretic action of apelin in the distal nephron. During water deprivation (WD), the urine concentrating capability was impaired by an apelin peptide, apelin-13, accompanied by the suppression of the protein expression of AQP2, NKCC2, PRR/sPRR, renin in the kidney. The upregulated expression of AQP2 or PRR/sPRR both induced by AVP and 8-Br-cAMP was blocked by apelin-13 or H89, a PKA inhibitor. Interestingly, the blockage of apelin-13 on AVP-induced AQP2 protein expression was reversed by exogenous sPRR. Thus, our data suggest that the apelin is involved in urine concentrating ability via functioning AVP downstream in cAMP/PKA/sPRR signal pathway.